The Effect Of Gross Domestic Product, Cash Flow, Company Size, EPS, And PER On Stock Returns In LQ 45 Companies Listed On The Indonesian Stock Exchange For The Period 2018-2021 - Yoga Kesuma; Rina Trisnawati (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to analyze the effect of gross domestic product, cash flow, company size, EPS, and PER on stock returns in LQ 45 companies listed on the Indonesia Stock Exchange for the period 2018-2021. The data used is secondary data, with the documentation method sourced from the Annual Report data of companies in LQ 45 listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The analysis technique used in this research is multiple regression analysis. The population in this study were construction companies listed on the IDX for the 2018-2021 period with a total of 45 companies. The sample of this study amounted to 104 companies. The data analysis method used in this research is a statistical analysis using SPSS software. The results of this study show that Gross Domestic Product affects firm value. Cash Flow does not affect firm value. Company size does not affect firm value. EPS affects the value of the company. PER affects the value of the company.